2010
DOI: 10.1016/j.ydbio.2010.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase A regulates GDNF/RET-dependent but not GDNF/Ret-independent ureteric bud outgrowth from the Wolffian duct

Abstract: Embryonic kidney development begins with the outgrowth of the ureteric bud (UB) from the Wolffian duct (WD) into the adjacent metanephric mesenchyme (MM). Both a GDNF-dependent and GDNF-independent pathway have been identified. In vivo and in vitro, the GDNF-dependent pathway is inhibited by BMPs, one of the factors invoked to explain the limitation of UB formation in the unbudded regions of the WD surrounding the UB. However, the exact mechanism remains unknown. Here a previously described in vitro system tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…Pharmacological manipulations of PKA have been shown to affect epithelial cell polarity and morphogenesis in vitro (Nedvetsky et al, 2012; Tee et al, 2010). However, we identify an endogenous upstream signal engaging PKA in the regulation of epithelial tubulogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological manipulations of PKA have been shown to affect epithelial cell polarity and morphogenesis in vitro (Nedvetsky et al, 2012; Tee et al, 2010). However, we identify an endogenous upstream signal engaging PKA in the regulation of epithelial tubulogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A possible molecular pathway mediating PKA activation by BMP non-canonical signaling Several studies have reported that BMP signaling can upregulate PKA activity (Gangopahyay et al, 2011;Lee and Chuong, 1997;Liu et al, 2005;Tee et al, 2010). However, the molecular pathway by which this occurs remains unclear.…”
Section: Model Of the Molecular Pathways Regulating Dlx5 And Hmx3 Expmentioning
confidence: 99%
“…Bar: ERK, AKT, phosphatidylinositol-3 0 -kinase, and protein kinase A are also known to play a role in wolffian duct budding. [20][21][22] To investigate these pathways, we measured multiple phosphorylated proteins simultaneously by the enzyme-linked immunosorbent assay microarray technique 23 in microdissected urogenital systems from embryonic day (ED) 11.5 dKO and control embryos. In 2 of 3 comparisons, ERK2 phosphorylation was decreased (Figure 6a and e).…”
Section: Disturbed Proliferation and Apoptosis Balance In Cnd And Ugsmentioning
confidence: 99%
“…CND regression critically depends on retinoic acid and Ret signaling. 7-9,31 ERK is a downstream target of Ret and Eph/Ephrin signaling, [18][19][20] and inhibition of ERK led to failure in UB formation and CND aplasia. 31 Our analysis at ED 11.5 localized high ERK1/2 activation in the UGS and the caudal CND with a gradual decrease toward the UB.…”
Section: Eph/ephrin Signaling During Ureter Translocationmentioning
confidence: 99%